2018
DOI: 10.14419/ijet.v7i2.29.13331
|View full text |Cite
|
Sign up to set email alerts
|

Production of reserpine of rauwolfia serpentina [L] kurz ex benth through in vitro culture enriched with plant growth regulators of NAA and kinetin

Abstract: Rauwolfia serpentine [L] Kurz ex Benth is a valuable plant yielding alkaloid of reserpine. The aim of this study was to find the most effective way of reserpine production. Growth regulators {naphthalene acetic acid [NAA] and Kinetin}were applied to promote and to regulate the growth of explant of R. serpentine cultured in vitro. The study was conducted at the laboratory of Bandung Institute of Technology [ITB]. Nine formulations of NAA and Kinetin were the treatments that were repeated twice in completely ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…2d). Subandil et al (2018) applied NAA and Kn to promote and to regulate the growth of explant of R. serpentina cultured. Bhadra et al (2013) reported that green and granular callus was produced on MS + 3.0 mg/l BAP + 1.0 mg/l NAA + 1.5 mg/l Kn from nodal explants of R. serpentina while loose and friable callus were produced on 0.1 mg/l picloram and 1.0 mg/l Kn containing medium from the same explants.…”
Section: Resultsmentioning
confidence: 99%
“…2d). Subandil et al (2018) applied NAA and Kn to promote and to regulate the growth of explant of R. serpentina cultured. Bhadra et al (2013) reported that green and granular callus was produced on MS + 3.0 mg/l BAP + 1.0 mg/l NAA + 1.5 mg/l Kn from nodal explants of R. serpentina while loose and friable callus were produced on 0.1 mg/l picloram and 1.0 mg/l Kn containing medium from the same explants.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of water will cause nitrogen nutrient uptake to be inefficient and reduce the growth and yield of soybean crops (Agung and Rahayu, 2004). Soil environment lacking water in the first stages of growth may cause a retarded plantlet (Subandi and Dikayani, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Giberellins stimulate cell expansion through stimulation of cell wall enzymes, namely Xyloglucan Endotranslycosylase (XET) which can break the bonds in the cell wall-forming molecule, hemicelluluse which causes other wall components, namely cellulose microfibrils to move, causing widening or expansion of cell walls (Dengler, 2008;Subandi et al, 2018a), and this allows an increase in cell size which causes plants to grow taller.…”
Section: Plant Height (Cm)mentioning
confidence: 99%